Law and accounting escape room: a gamified learning experience - Ahmad Mustafa, Mimi Sofiah; Abd Malib, Marziana; Othman, Yuhanza; Mahat, Ida Rahayu; Naimat, Nasihah (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
This innovation is a gamified learning experience created to assist the accounting students in an effective and creative manner to understand legal concepts in their journey to complete the course in a memorable style. This interactive and immersive activity challenges student to solve accounting and legal puzzles within a set time to "escape" a fictional business crisis. The product is unique because it fosters teamwork, critical thinking, and a practical understanding of legal principles applied in accounting contexts. Students work in teams to address legal and accounting challenges affecting a fictional company. They must solve the puzzles in about 60 minutes to restore the company's compliance, avoid penalties, and save the business. The game is complete once the students have successfully returned the company’s status quo before it goes into difficulties. It benefits the students because students are expected to understand how legal concepts (contracts, employment, tort, corporate governance) intersect with accounting practices, develop problem-solving and decision-making skills in legal contexts and collaborate effectively in a high-pressure environment, simulating real-world challenges. The product is easily commercialized because it is synonym with today’s generation high interest in gaming.